A pedagoga da escola pública do Paraná diante das demandas atuais de trabalho: um diário de bordo - Vargas, Daniela de (2024)
This research focuses on public schools and their daily life as experienced through the lens of a teacher educator. The aim is to present how the work of the teacher educator in the public school is being articulated, given the demands implemented in recent years, more specifically from 2020 to 2024, as well as the intensification and bureaucratization of her duties. The aim was to answer the following question: has the teacher educator been carrying out the duties set out in the official documents for the organization of pedagogical work, acting as an intellectual transformer, or is she carrying out a purely managerial role? Thus, the aim of this investigation is broken down into the following specific objectives: to situate the role of the teacher pedagogue in public schools in the face of official guidelines; to present the teacher pedagogue as a transforming intellectual, reflecting on her work from a critical and progressive perspective based on different authors who have dedicated their research to this subject, such as Paulo Freire, Henry Giroux, Georges Snyders, Raymond Williams, among others; and finally, to present the daily work of a pedagogue teacher in a public school in Paraná, in the face of the new demands implemented in recent years, analyzing official documents and reporting the experience through what we call a logbook of this professional's work. This is a qualitative study, based on bibliographic and documentary analysis, as well as personal experience reports, using field diary methodology. The results of the research revealed the intensification of the managerialist character that public education in Paraná is following, in which it is believed that the use of technological tools will be the solution to educational problems, in a similar way to what happened in the technicist decade of 1960-1970. The research highlights that the use of technology should not be disregarded as a complementary tool to the educational process, as expressed by Moraes (2016). However, it is essential to recognize that investing in training, recognition and appreciation of professionals is also a path that needs to be taken. The research also reveals the ambiguity of the teacher educator's work, whose conception of training chooses the human being as the center of educational action, as opposed to the vigilant and disjointed work of political-pedagogical issues. It is therefore essential to guarantee autonomy for teacher educators as professionals engaged in promoting democratic education in schools, which requires opportunities for them to reveal their full potential as reflective professionals committed to educational needs, acting as transformative intellectuals.